RELATIONSHIP OF CHARACTERISTICS OF PREGNANT WOMEN AND FOOD INTAKE WITH CHRONIC ENERGY DEFICIENCY - Adnani, Hariza; Nurhidayah, Nurhidayah (HEARTY, 2024)
The prevalence of pregnant women suffering from CED from 2017 to 2020 has increased. The main causes include the characteristics of pregnant women and lack of food intake of carbohydrates, protein, and fat. Research objective: to analyze the relationship between the characteristics of pregnant women and food intake as sources of carbohydrate, protein, and fat with the incidence of CED in pregnant women. This study belongs to an analytical observational study with a case-control approach, with a sample group of 19 pregnant women experiencing CED and 19 pregnant women not experiencing CED in the control group. This study applies purposive sampling as a sampling technique. Data analysis was performed with univariate and bivariate using the chi-square test. The results of the study showed that two variables had a p-value of < 0.05, namely infectious diseases and protein food intake. From the lower upper limit value, five variables were at risk of CED in pregnant women at Tegalrejo Health Center Yogyakarta, including age, infectious diseases, intake of carbohydrates, protein, and fat. It is suggested that the Health Center carry out surveillance and further studies to figure out the incidence and risk factors of CED in pregnant women in the Health Center in Yogyakarta.